R&D Capitalization and Reputation-Driven Real Earnings Management (Partially Retracted) - Seybert, Nicholas (The Accounting Review, 2010)
ABSTRACT: Prior research finds that mandatory expensing induces underinvestment in research and development (R&D). The current study investigates whether capitalization can also create R&D investment problems. Abandoning a capitalized project requires asset impairment, a negative reporting effect that could damage managers' reputations. In an experiment utilizing M.B.A. student participants, I find that managers responsible for initiating an R&D project are more likely to overinvest when R&D is capitalized. I show that high self-monitors (those most likely to alter their behaviors to convey a positive image) are most likely to overinvest, suggesting that reputation concerns contribute to this behavior. A follow-up survey reveals that, when R&D is capitalized, experienced executives anticipate overinvestment and expect project abandonment to have a stronger negative impact on the responsible manager's reputation and future prospects at their firm. The results suggest that managers are held responsible for the external reporting consequences of their projects, such that mandating R&D capitalization may not reduce real earnings management.